Molecular characterization of Cryptosporidium spp. in Bactrian camels (Camelus bactrianus) from Yili Kazak Autonomous Prefecture of Xinjiang, China - Mi, Rongsheng; Silayi, Amanguli; Wang, Yongsheng; Xia, Chenyang; Tang, Wenqiang; Gong, Haiyan; Huang, Yan; Zhang, Yan; Yan, Genqiang; Chen, Zhaoguo (Frontiers in Veterinary Science, 2024)
Introduction Cryptosporidium spp. is a significant zoonotic parasite. The prevalence and infection characteristics of Cryptosporidium spp. in Bactrian camels in Yili Kazak Autonomous Prefecture have yet to be fully understood. Thus, the molecular epidemiology of cryptosporidiosis in camels was investigated in this region. Methods A total of 1,455 fecal samples were collected from 6 counties in three regions (Altay, Tacheng, and Yili) in Yili Prefecture. Nested PCR targeting the small subunit ribosomal RNA (ssu rRNA) gene was used to identify the species or genotypes of Cryptosporidium infection in camels. For C. parvum positive samples, the subtypes were identified using the 60-kDa glycoprotein (gp60) gene. Results and discussion The overall infection rate was 8.7% (126/1,455), ranging from 5.6% to 11.7% in different regions, and 4.2% to 15.8% in different counties. A significant difference was observed amongst the counties (p < 0.001). Three species were detected, namely C. andersoni (65.1%, 82/126), C. parvum (34.1%, 43/126), and C. occultus (0.8%, 1/126). Three C. parvum subtypes, If-like-A15G2 (n = 29), IIdA15G1 (n = 4), and IIdA19G1(n = 1) were detected, with If-like-A15G2 being the most prevalent subtype. Camels aged 3-12 months exhibited the highest infection rate (11.4%, 44/387), with no significant difference among age groups (p > 0.05). C. parvum was predominant in camels under 3 months, while C. andersoni prevailed in camels over 3 months. There was an extremely significant difference observed among seasons (p < 0.001), summer had the highest infection rates (16.9%, 61/360). This study collected nearly 1,500 samples and, for the first time, investigated Cryptosporidium spp. infection in camels based on different age groups and seasons. All three Cryptosporidiumspecies identified were zoonotic, posing a potential threat to human health and requiring close attention.